HUBUNGAN ANTARA KOMPETENSI GURU DAN BUDAYA SEKOLAH DENGAN KINERJA GURU - Rahmawati, Rahmawati; Siraj, Arifuddin; Achruh, Andi (Idaarah: Jurnal Manajemen Pendidikan, 2021)
Abstract: The Relationship between Teacher’s Competence, School Culture and Teacher’s Performance This article aims to prove the relationship between teacher’s competence, school culture, and teacher’s performance at State Senior High School 10 in Maros, South Sulawesi. This research is quantitative or research by using quantitative approach. The population in this study was 24 teachers and 351 students. The sample was determined by using disproportionate random sampling so that a sample of 77 people was obtained, consisting of 24 teachers taken in total and 53 students taken as many as 15% of the population. The data techniques used were questionnaire and documentation. Data analysis is performed using descriptive statistics and inferential statistics through correlation tests. The results of this study prove that there is a positive relationship between teacher’s competence, school culture, and teacher’s performance at State Senior High School 10 in Maros. Thus, teacher’s performance can be improved through the application of good competencies and the creation of a conducive school culture at schools. Abstrak: Hubungan antara Kompetensi Guru dan Budaya Sekolah Artikel ini bertujuan untuk menguji pengaruh kompetensi guru dan budaya sekolah dengan kinerja guru pada SMA Negeri 10 Maros, Sulawesi Selatan. Penelitian ini dilakukan melalui pendekatan kuantitatif. Populasi penelitian ini adalah guru yang berjumlah 24 orang dan peserta didik yang berjumlah 351 orang. Sampel ditentukan dengan menggunakan disproportionate random sampling sehingga diperoleh sampel sebanyak 77 orang, terdiri dari 24 orang guru yang diambil secara keseluruhan dan 53 orang peserta didik yang diambil sebanyak 15% dari populasi. Data dikumpulkan dengan menggunakan angket dan dokumentasi, kemudian dianalisis dengan menggunakan statistik deskriptif dan statistik inferensial melalui uji korelasi. Hasil penelitian ini membuktikan bahwa terdapat hubungan positif dan signifikan antara kompetensi guru dan budaya sekolah dengan kinerja guru di SMA Negeri 10 Maros. Dengan demikian, kinerja guru dapat ditingkatkan melalui penerapan kompetensi yang baik dan terciptanya budaya sekolah yang kondusif di sekolah.